Embracing & evaluating creativity & passion of FPHP family for writing / Irina Mohd Akhir - Mohd Akhir, Irina (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2023)
To some, favorite thing to do is design work, while to some writing! The essential for both is actually part of "Learning how to be creative"- part of motivational activities that drives one to express their thought and feelings. Thank you to editorial team, this platform successfully made continuous, not to let the untap talent go to waste. Thus, this piece of work entails the tagline for the bulletin team. You'll find updates on what's happening in Tourism realm. Volume 1 publication for year 2023 foregrounding many creative writings collected for fun of reading journey into the Tourism World. Made available in FPHP webpage, showcasing this issue in Flip FPHP Bulletin Homepage & Coffee Corner Bookcase. Special for flipper & greener readers!